2022
DOI: 10.1007/s11831-022-09713-y
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-Based Tests and Results for the Evaluation of Infill Masonry Walls Influence on the Dynamic Behaviour of Buildings: A Review

Abstract: Tests on infill masonry walls have been widely performed by many researchers and for a long time with the main purpose of characterising the infill performance under earthquake-type excitations. However, most of these works deal with laboratory tests on purpose-built specimens. More recently, vibration-based tests have been also adopted to investigate the influence of the non-structural elements on the dynamic behaviour of buildings, with the advantage that this kind of tests can be performed both on laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 109 publications
0
4
0
2
Order By: Relevance
“…En ASCE 41-13 [9] se define el término partición como aquel componente vertical que no soporta carga y que provee división de espacios. Al respecto, en nuestro medio existe la concepción de ignorar las particiones en la etapa de diseño; lo cual es conservador y simplifica los procedimientos de cálculo [10]. En este sentido, especialmente cuando se trata de particiones pesadas, se requieren detalles en los planos que garanticen la estabilidad de esta y que no contribuya a la rigidez lateral de la estructura ni a resistir fuerzas; debido que estos elementos tienen la capacidad de inducir acciones no consideradas en el diseño, como lo es la torsión adicional [11].…”
Section: Marco Teóricounclassified
“…En ASCE 41-13 [9] se define el término partición como aquel componente vertical que no soporta carga y que provee división de espacios. Al respecto, en nuestro medio existe la concepción de ignorar las particiones en la etapa de diseño; lo cual es conservador y simplifica los procedimientos de cálculo [10]. En este sentido, especialmente cuando se trata de particiones pesadas, se requieren detalles en los planos que garanticen la estabilidad de esta y que no contribuya a la rigidez lateral de la estructura ni a resistir fuerzas; debido que estos elementos tienen la capacidad de inducir acciones no consideradas en el diseño, como lo es la torsión adicional [11].…”
Section: Marco Teóricounclassified
“…[25][26][27][28]): (i) based only on the fracture of TRM for the out-of-plane bending [20], or (ii) taking into account also masonry crushing (e.g., Refs. [25,27,29]). An assessment of the structural performance is undertaken, usually along with a damage assessment applying non-destructive techniques such as ambient vibration testing [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…[25,27,29]). An assessment of the structural performance is undertaken, usually along with a damage assessment applying non-destructive techniques such as ambient vibration testing [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive literature review about vibration-based methods for damage detection can be found in. [1][2][3] Among them, the response-based methods are the most adopted ones, even if they present some challenges in real building applications [4] related to the location and the extent of damage (detection of structural and/or non-structural damaged components), the sensitivity of the dynamic response to damage, the choice of damage indexes to be used, the sensor locations, etc. However, although this strategy is widely recognised to be of useful application, a relatively low number of works can be found dealing with applications on real or scaled structures.…”
Section: Introductionmentioning
confidence: 99%
“…In framed RC and steel buildings, infills are the most important non-structural elements that may affect the structural dynamic response [3,18] and the seismic performance, [19][20][21][22][23] sometimes leading to the development of undesirable effects, such as the activation of soft storey mechanisms or the shear failure of short unconfined columns. [24,25] Thus, not only damage to structural elements but also to non-structural components often reflects in changes on the dynamic behaviour of infilled structures, as proved by some authors that investigated the dynamic response of infilled buildings after damage produced by earthquakes all around the world.…”
Section: Introductionmentioning
confidence: 99%